FAKTOR – FAKTOR YANG MEMPENGARUHI KEBERHASILAN KOPERASI DI INDONESIA - Azhari, Azhari; Yanto, Ferri (LPPM-UNIKI, 2023)
The number of cooperatives in Indonesia reaches hundreds of thousands, but not all of them are active due to several factors including member participation, business volume, total assets and outside capital. The purpose of this study is to provide the dominant factors that influence the success of cooperatives in terms of SHU/profits. The data used is from 2001-2021 with multiple regression as the analysis tool. The results of the analysis show that simultaneously the variables own capital, outside capital and businesa volume affect the SHU. Partially own capital does not affect the profit, while sales volume and outside capital affect the profit. The limitation of this research is that the data used is not based on the types of cooperatives in Indonesia